2014
DOI: 10.3109/10641955.2014.931418
|View full text |Cite
|
Sign up to set email alerts
|

IMA and IMAR in serum and saliva of preeclampsia – a preliminary study

Abstract: This study is an evidence for involvement of oxidative stress in the pathogenesis of preeclampsia, which is reflected in serum and saliva. Salivary IMAR could be a better marker for early prediction of preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
4
12
0
Order By: Relevance
“…2224 Hence serum IMA a marker of oxidative stress and hypoxia is elevated in preeclampsia. Our study is in accordance with the studies done by Ustan Y et al, 11 Gafsou et al, 12 Jyothi et al 10 and Jyotirmayee et al 9 who observed elevated levels of serum IMA in preeclampsia in third trimester and Papageoghiour AT et al 3 who observed changes in first trimester.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…2224 Hence serum IMA a marker of oxidative stress and hypoxia is elevated in preeclampsia. Our study is in accordance with the studies done by Ustan Y et al, 11 Gafsou et al, 12 Jyothi et al 10 and Jyotirmayee et al 9 who observed elevated levels of serum IMA in preeclampsia in third trimester and Papageoghiour AT et al 3 who observed changes in first trimester.…”
Section: Discussionsupporting
confidence: 93%
“…The elevated levels of serum IMA continued till delivery. Jyotirmayee et al 9 and Jyothi et al 10 in their studies done on pregnant women at 30 ± 4 weeks and 34 ± 4 weeks of gestation respectively, found an elevated levels of serum IMA in preeclampsia.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Proteinuria ≥0.3 g in a 24 h urine specimen, protein/creatinine ratio ≥0.3, or urine dipstick protein 1+ was also required for PE diagnosis. Additionally, in a woman with new‐onset hypertension without proteinuria, the new onset of any of the following was considered diagnostic of PE: platelet count <100 000/μL; serum creatinine >1.1 mg/dL or doubling of serum creatinine in the absence of other renal disease; liver transaminase more than twofold the normal level, pulmonary edema; cerebral or visual symptoms …”
Section: Methodsmentioning
confidence: 99%
“…Additionally, in a woman with new-onset hypertension without proteinuria, the new onset of any of the following was considered diagnostic of PE: platelet count <100 000/lL; serum creatinine >1.1 mg/dL or doubling of serum creatinine in the absence of other renal disease; liver transaminase more than twofold the normal level, pulmonary edema; cerebral or visual symptoms. 16,17 The mothers fulfilled the criteria for PE and their premature newborns were included in this study as the PE group. The PE mothers underwent cesarean section due to hypertension and prematurity.…”
Section: Methodsmentioning
confidence: 99%